Civil Responsibilities Badan Usaha Nilik Negara (BUMN) Surveillance Bodies Faced With Damages in The Context of Civil Corruption - Asepte Ginting; Elwi Danil; Detania Sukarja; Marlina Marlina (International Conference on Economic Business and Social Science, 2024)
The legal body is a terminology that is closely related to the right person, and the legal body itself is a closely connected terminology with the field of civil law. The research used to answer the question in this study is a combination of normative law research and empirical law research. Approaches that can be applied in research are case approaches, legal approach, conceptual approaches and historical approaches. As for the discussion that will be analyzed in this study on how the fulfilment of the elements of criminal responsibility to the supervisory body and how the corporate criminal responsibilities and the responsibility of the supervisor body are separated. The results of this study show that there is criminalization of the Supervisory Body in the event of the loss of the BUMN and this is a Tool of Social Engineering in order to raise the awareness of the oversight body so that the supervision function to the direction in conducting the management of the BUMN can be implemented as it should.